Effects of small-fiber neuropathy induced by resiniferatoxin on skin healing and axonal regrowth after burn. Issue 3 (May 2017) - Laverdet, Betty; Girard, Dorothée; Bayout, Audrey; Bordeau, Nelly; Demiot, Claire; Desmoulière, Alexis
Highlights: Resiniferatoxin promoted transient hypoalgesia without inducing nerve degeneration. Neuropeptides were depleted in cell bodies and endings of primary sensory neurons. Resiniferatoxin-mediated neuropathy delayed granulation tissue remodeling after burn. The proportion of small fibers expressing peripherin was reduced during healing. After burn healing, nerve regrowth and plasticity within the wound were not modified. Abstract: Background: Damage to the peripheral nervous system influences wound healing and, after a deep burn, imperfect cutaneous nerve regeneration occurs. A third-degree burn model was developed in rats combined with the use of resiniferatoxin (RTX), known to promote sensory neuropathy. Methods: Rats were injected intraperitoneally either with RTX or vehicle. A mechanical sensory assay and the hot plate thermal sensory test were performed. The structural integrity of the sciatic nerve was assessed using transmission electron microcopy. After RTX injection, third-degree thermal burns were performed. Wound closure was monitored and samples were collected for histological analysis, immunohistochemistry and immunoblotting for neuronal markers. Results: RTX promoted both mechanical and thermal hypoalgesia. This transient RTX-mediated sensory deficit occurred without damaging the integrity of nerve fibers and induced a significant depletion of neuropeptides in both neuronal bodies and intraepidermal nerve fibers. Although wound closure rates were similar in both groups, the kinetic of granulation tissue remodeling was delayed in the RTX group compared with control group. A significant reduction of the peripherin expression in the RTX group was observed indicating impaired axonal regrowth of small fibers within the wound. Conclusion: Our study confirms the important roles of innervation during skin healing and the defect of nerve regeneration after burn.